Scale of moral educational conceptions (SMEC) - Caetano, Luciana Maria (2016)
The purpose of this article is to present the process of construction and validation of the Scale of Moral Educational Conceptions (SMEC). The SMEC is an instrument that investigates the educational conceptions of parents in relation to the constructs of obedience, respect, justice and autonomy conceived in relation to their children. The study included 860 fathers and mothers representing the five regions of Brazil. The content analysis described and confirmed the construction of the items and the reference to the constructs. The confirmatory factor analysis suggested as acceptable to the multifactorial structure, confirming the four constructs (GFI = 0.933, AGFI = 0.919 and RMSEA = 0.0702). Therefore, the SMEC is a measuring instrument with adequate psychometric characteristics. In relation to the instruments of measurement of judgment and moral competence more used in Brazil, the SMEC presents the original possibility of investigating the moral conceptions of the participants in relation to the types of social relationships that are established with regard to the constructs of obedience, respect, justice and autonomy.